Analisis Pemanfaatan Artifical Intelligence terhadap Lingkungan Kerja Dimediasi Beban Kerja - Djaya, Eka Sumandary; Yusuf, Ruliati Yusuf; Yunarsi, Yunarsi (Politeknik Baubau, 2025)
Artificial Intelligence (AI) is one of the rapidly evolving technological innovations that supports employee work efficiency across various industrial sectors. PT. Harta Samudra, a fisheries company located in Maluku Province, has begun adopting AI technology in its operations to manage high workloads and enhance productivity. This study aims to analyze the impact of AI utilization on the work environment and employee workload, as well as to examine the mediating role of the work environment in strengthening the relationship between AI utilization and workload. The study involved the entire population of PT. Harta Samudra’s employees, totaling 100 individuals, selected using a saturated sampling technique. A quantitative research design was applied, with data collected through a closed-ended Likert scale questionnaire. Data analysis was conducted using Partial Least Squares (PLS) with the assistance of SmartPLS version 3.3.8 software. The results indicate that AI utilization has a positive and significant effect on the work environment and both directly and indirectly influences employee workload. The work environment was proven to be a mediating variable that strengthens the relationship between AI utilization and workload. The Adjusted R Square value shows that 66.1% of the variation in workload can be explained by AI utilization and work environment conditions, while the remaining 33.9% is influenced by other factors not examined in this study. This research is expected to contribute to other fisheries companies in formulating AI-based technology adoption strategies to simultaneously improve operational efficiency and employee well-being.